Atitude investigativa: uma análise do espaço da pesquisa na escola básica - MACÊDO , Ruanita Costa (2019)
This dissertation aimed to analyze the research space in the context of the Elementary School, understanding the dynamics of the investigative attitude in the teaching profession. For that, it was necessary to interpret the conceptions of research and researched school present in the discourse of the teachers, the pedagogical coordinators and the principal from the school, to describe the pedagogical practices, besides identifying the prescriptions of research activities in the guiding documents of the Brazilian educational policy and its developments. The stage for the first discussions about the teacher as a researcher, which articulates teaching and research in the context of Elementary School that is located in England in the 60s.Similar movements took place in other parts of the world and, in Brazil, the initiative came from Rio de Janeiro State University in 1992, which, in partnership with the Municipal Secretariat, organized a course that gave academic value to the teachers' concerns from Elementary School. Thus, studies on the investigative attitude are relevant because they reveal the meaning that the teacher attributes to his own practice in the various contexts and possibilities of pedagogical practices. This is a meaningful posture to the experience of professionals with political commitment and whose research has the construction and deconstruction of their own pedagogical practice throughout the process of construction of professional teaching knowledge. Brazilian authors such as Demo (2004, 2011), Pereira (2008), Arroyo (2003), Franco (2012) and André (2010) are some of the main ones that underlie the analysis throughout the work, internationally there are scholars like Alarcão (2000) and Beillerot (2012). The mentioned theoretical references investigate about research, training, pedagogical practice and the right to education to support the discussions of the study. This research was also supported by the documentary research with the analysis of LDBEN (1996), PNE (2014), PEE (2014) of the State of Maranhão and PME (2015) of São Luís, the National Curriculum Guidelines for the Graduation in Pedagogy (2006) and for Basic Education (2010), from PCN (1997) and PPP (2007) from the researched school, which has as its differential one of the highest results of the capital's IDEB.The research had the participation of nine subjects, acting in the teaching, coordination and general direction of the researched school, having as data collection instrument the semi-structured interview and an adaptation of the qualitative approach research proposed by Bicudo (2011) as a technique. of data analysis. It was found that the research space in the Elementary School is located in the physical structure of the institution and in the pedagogical practice of the subjects who build the school daily. The first aspect refers to the proper place of knowledge construction such as the classroom and the library and in the pedagogical practice the PPP elaboration, the teaching plans, as well as the formative moments.